Kela – A Middle Paleolithic flint extraction and reduction site in the northern Golan Heights. (April 2020) - Finkel, Meir; Gopher, Avi; Sharon, Gonen; Tirosh, Ofir; Ben-Yosef, Erez
Highlights: Reports a new Middle Paleolithic flint extraction and reduction locality in the Golan Heights (Kela). Presents a Middle Paleolithic exploitation site. Reports on the geochemical signature of Kela's flint. Discusses possible relationship between Kela and nearby prehistoric sites. Abstract: Flint-bearing Eocene outcrops are well known from west of the northern Jordan Rift Valley, appearing as a strip of land along the Eastern Galilee and extensively used by prehistoric knappers as a rich source of quality raw material. In this paper we report for the first time on the flint extraction and reduction site of Kela, located within an isolated Eocene limestone outcrop in the basalt terrain of the northwestern margins of the Golan Heights. Based on the analysis of flint items collected at the Kela extraction and reduction locality, we attribute the entire assemblage to the Middle Paleolithic period. Our conclusions are for the most part founded on the presence of numerous Levallois cores and on the absence of other cores and waste types. Our preliminary geochemical analysis tested possible links between the Kela extraction and reduction locality and prehistoric habitation sites in the region. Our finds show that Kela was a source of flint for the Middle Paleolithic knappers of the northern Golan Heights. These results contribute to our understanding of raw material exploitation strategies by prehistoric knappers in the northern Jordan Rift Valley and the Golan Heights.